Analisa Kekakuan Pelat terhadap Pembentukan Dimple Dies dengan Variasi Diameter Lubang dan Jumlah Lubang Dimple - Nur Kholis, M. Irfan; Erwanto, Erwanto; Aswin, Fajar (Jurnal Inovasi Teknologi Terapan, 2024)
The construction of the body of minibus passenger vehicles usually uses walls, roofs and floors called vehicle panels. The vehicle panel itself is the most important part that supports safety and comfort for the occupants of the vehicle. Generally, the vehicle panel will cause a sound that makes passengers uncomfortable because of the noise that occurs due to the vibration of the vehicle engine and damaged road conditions. Excessive vibration can be reduced by increasing the rigidity of the panel by changing the shape such as beads, embossing, stiffeners, spot welded stiffenes, and grooves. The purpose of this study was to determine the effect of borehole variation and the number of dimple holes on plate stiffness for its natural frequency response. This research method is shown as follows: making experimental designs, dimple manufacturing processes, measuring and analyzing the results of dimple-shaped plates with variations in boreholes and the number of dimple holes to stiffness for their natural frequency response response. Based on the results, the number of holes on the dimple plate affects the stiffness of the plate to its natural frequency response.